2010
DOI: 10.1093/jscr/2010.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical exposure of the Distal Radius in a patient with a flexor carpi radialis brevis muscle anomaly

Abstract: There are numerous reports of anatomical variants of the muscles of the forearm, particularly the extensors of the wrist and hand. The abnormal deep and short radial wrist flexor (flexor carpi radialis) is rare. There are only two previously reported cases. We present the case of an anomalous ‘flexor carpi radialis brevis’, muscle found intra-operatively during a volar approach to the distal radius and discuss the strategies needed for further exposure in order to complete the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 2 publications
0
10
0
2
Order By: Relevance
“…Other authors successfully retracted the FCRB muscle to the ulnar side [ 11 , 13 ]. Laugharne and Power stated that the FCRB made the exposure of the distal radius more difficult, and that distal release was necessary to visualize the fracture site [ 14 ]. Werntz et al showed that the FCRB was resected because its retraction to expose and reduce the fracture site was difficult [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors successfully retracted the FCRB muscle to the ulnar side [ 11 , 13 ]. Laugharne and Power stated that the FCRB made the exposure of the distal radius more difficult, and that distal release was necessary to visualize the fracture site [ 14 ]. Werntz et al showed that the FCRB was resected because its retraction to expose and reduce the fracture site was difficult [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…8). 6,10,12 Given these attachments, its primary role is likely wrist flexion. However, its contribution to this action-and the consequences of destruction or denervation-may vary among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In 1 case, the muscle had to be fully released before fracture reduction and internal fixation could be completed. 10 In a second case (treatment of a malunion of the distal radius), the FCRB was elevated radially and the flexor tendons and median nerve were retracted ulnarly. 9 One case series described 3 patients undergoing plate fixation of distal radius fractures with exposure of the distal radius obtained through the radial retraction of the FCRB muscle belly.…”
Section: Discussionmentioning
confidence: 99%
“…El FCRB largo, en cambio, tiene su origen en el borde lateral del radio, distal a la inserción del músculo Pronator Teres. Algunos autores 3,6,11,12 han encontrado formas mixtas, con fascículos que se originan en la membrana interósea, en el borde radial del cúbito, en el Pronator Teres, en la fascia antebraquial y/o en el Flexor Pollicis Longus. En nuestro caso existía un fascículo procedente del músculo PQ.…”
Section: Discussionunclassified
“…1-3, 9-12, 14, 16 Probablemente, este incremento está en relación al aumento del número de fracturas de radio distal tratadas quirúrgicamente por vía palmar. 3,11 En la serie de Ho y cols. 3 , por ejemplo, 4 de las 46 fracturas tratadas quirúrgicamente en los dos meses que duró su estudio prospectivo presentaban dicha anomalía.…”
Section: B Aunclassified